Determinants of adaptive behavior of a master's student of psychological and pedagogical education as a subject of scientific reflection (Revista de Investigaciones Universidad del Quindío, 2022)
The article reveals the current views of the professional community on adaptive behavior, the ideas of transition to the development of a relatively stable personality structure of a master's student of psychological and pedagogical education. The data were obtained using the methods of psychological diagnostics: a multi-level personal questionnaire (MLO) "Adaptability", the questionnaire " SOP-2 "(Tendency to deviant behavior), the method "Depersonalization by professional systems", the analysis of educational activities with a focus on the method of cases, social assessments, individual conversations. Considering the current state, problems and diagnostic assessments, it can be reached the logical conclusion that the determinants of the formation and development of adaptive behavior are the dialectical laws of the development of matter, and the totality of indicators of individual personal adaptive potential, the tendency to deviate behavior, life satisfaction and educational effectiveness will determine the level of the studied behavior.
Keywords: Adaptive behavior; Personality; Undergraduate student; Educational activity; Future psychologist